2016
DOI: 10.1186/s10194-016-0638-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered kynurenine pathway metabolites in serum of chronic migraine patients

Abstract: BackgroundActivation of glutamate (Glu) receptors plays a key role in the pathophysiology of migraine. Both NMDA and metabotropic Glu receptors are activated or inhibited by metabolites of the kynurenine pathway, such as kynureninic acid (KYNA), quinolinic acid (QUINA), and xanthurenic acid (XA). In spite of the extensive research carried out on KYNA and other kynurenine metabolites in experimental models of migraine, no studies have ever been carried out in humans. Here, we measured all metabolites of the kyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 37 publications
10
83
1
1
Order By: Relevance
“…As a further step, 5-HTP (from Griffonia simpliciofila supplement) entered kynurenine pathway as kinurenic acid that was able to act as an endogenous NMDA receptor antagonist, blocking glutamatergic activity. In migraine patients, kynurenine pathway perturbation was related to an aberrant unidirectional metabolization of kinurenic acid in antralic acid P. Zavarise, G. D. Volta 7/9 OALib Journal (promoting itself free radical production), with a consequent loss of the inhibitory action on glutamatergic acid and its excitatory activity [16] [29]. Thus, low plasmatic levels of kinurenic acid could be considered as an effective proxy of NMDA receptor activity [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a further step, 5-HTP (from Griffonia simpliciofila supplement) entered kynurenine pathway as kinurenic acid that was able to act as an endogenous NMDA receptor antagonist, blocking glutamatergic activity. In migraine patients, kynurenine pathway perturbation was related to an aberrant unidirectional metabolization of kinurenic acid in antralic acid P. Zavarise, G. D. Volta 7/9 OALib Journal (promoting itself free radical production), with a consequent loss of the inhibitory action on glutamatergic acid and its excitatory activity [16] [29]. Thus, low plasmatic levels of kinurenic acid could be considered as an effective proxy of NMDA receptor activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…In migraine patients, kynurenine pathway perturbation was related to an aberrant unidirectional metabolization of kinurenic acid in antralic acid P. Zavarise, G. D. Volta 7/9 OALib Journal (promoting itself free radical production), with a consequent loss of the inhibitory action on glutamatergic acid and its excitatory activity [16] [29]. Thus, low plasmatic levels of kinurenic acid could be considered as an effective proxy of NMDA receptor activity [29]. Finally, magnesium deficiency has been related to CSD [30], as well as to free radical formation and NMDA modulation of glutamatergic activity [31] [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated lower levels of kynurenic acid (KYNA) in serum of patients suffering from chronic migraine compared to controls [12, 13]. KYNA could be a new therapeutic line in migraine chronification, but KYNA can poorly cross the blood–brain barrier (BBB), while newer KYNA analogues have better BBB penetration characteristics [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Low plasma levels of KYNA may be considered a reliable marker of NMDA receptor activation. Cerebral levels of KYNA can be increased by the assumption of its precursor 5-HTP [13] . Based on the mechanisms described above, the combination of 3 components, tanacetum parthenium, 5-HTP, and magnesium is expected to synergistically influence the biologic pathways involved in migraine pathogenesis, and, therefore, to have a therapeutic potential in migraine prevention.…”
Section: Introductionmentioning
confidence: 99%